Removal of Hg(II) and CH3Hg(I) Using Rasped Pith Sago Residue Biosorbent. Issue 11 (16th April 2014) - Saman, Norasikin; Johari, Khairiraihanna; Tien, Song Shiow; Mat, Hanapi
Abstract Rasped pith sago residue (RPSR) was used as a biosorbent for inorganic (Hg(II)) and organic (CH3Hg(I)) mercury removal from aqueous solutions. In biosorbent preparation, the RPSR having particle size range of 0.06–0.10 was washed with deionized water repeatedly to eliminate impurities, dried in an oven at 50°C for two days, followed with drying in a vacuum oven for 3 h. The performance of RPSR as a novel biosorbent for removing mercury was evaluated in batch adsorption. The adsorption of mercury ions was found to highly dependent on the pH of the solutions. The Hg(II) adsorption was high at pH > 4, while the CH3Hg(I) adsorption was found higher at pH < 5. The higher adsorption capacity for Hg(II) and CH3Hg(I) was 0.288 and 0.213 mmol/g, respectively. Both mercury adsorptions equilibrium and kinetics were fitted to the Langmuir isotherm model and pseudo‐second‐order kinetic model, respectively. These results indicate the RPSR has a potential to be a low‐cost biosorbent for mercury removal process from aqueous solutions.